Preliminary evaluation of a precise starting sensor for short distance athletic sports below 400 m - Lee, L.; Song, H.; Oh, C.; Park, C.; Huh, E.; Lee, J. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The importance of starting a race in short distance athletic sports below 400 m was rarely considered to the extent that it should be. The main research theme in this field has mainly been the relationship between the starting signal and the response speed of leg muscles. The records in short distance athletic sports have been improved through training athletes to increase their response speed. However, the improvements in records have also been due to the starting time speed; thus, there is another way to improve times, that is, through the starting speed. The starting speed related to the kicking force against the starting blocks at the start of a race. The objectives of this research were to present a method for analyzing forces acting upon a starting block at the start of a race and to optimize the starting conditions for each athlete. To achieve these objectives, a starting block with Wheatstone bridge type strain gauges which could measure, in normal and horizontal directions, the repulsive forces acting on the starting blocks at a starting point in real-time, was developed. The use of this block was expected to correct the posture of each athlete and record the sports dynamics data for each athlete.